Vegetation restoration in Northern China: A contrasted picture - Wang, Feng; Pan, Xubin; Gerlein‐Safdi, Cynthia; Cao, Xiaoming; Wang, Sen; Gu, Lianhong; Wang, Dongfang; Lu, Qi (Land degradation & development, 2020)
China started a long‐term effort to mitigate desertification and ensure the sustainability of its environment by implementing multiple large‐scale national ecological restoration projects since 1978, but their success has been highly debated for a long time. Here, we estimated the change of vegetation fraction cover (VFC) in the Three‐North Shelterbelt Programme (TNSP) region over the past three decades on the basis of the Normalized Difference Vegetation Index dataset from the Global Inventory Monitoring and Modeling System. We evaluate the national strategy of vegetation restoration in North China by comparing rainfall patterns, vegetation change, and national ecological restoration programs on the basis of the Global Meteorological Forcing Dataset and the China Forestry Statistical Yearbooks. We find that the western, central, and eastern parts of the TNSP region exhibited a distinct increase in vegetation coverage. The western region had the highest increase of annual precipitation, but this did not result in the highest VFC increase. We infer that ecological restoration activities are the factor leading to the observed increase in VFC in the eastern and central region compared with the western region. The low survival rate of planted trees in the forest of the TNSP region indicates that it is necessary to improve the mode of vegetation restoration to obtain optimal returns and avoid excessive investment. The success of new strategies, for example, natural restoration and quasinatural afforestation are promising as an alternative method. China's experiences in reforestation will be very beneficial for other countries to promote land degradation mitigation and vegetation improvement in the arid and semiarid areas.